ALTERNATIVE ENVIRONMENTAL APPLICATIONS IN DEVELOPING SENSITIVITY TO NATURAL ENVIRONMENT VALUES IN SOCIAL STUDIES - (:unkn) unknown (MARMARA UNIV, 2018)
Sensitivity to the natural environment is of great importance in terms of environmental education of the students. For this purpose, in this research, alternative environmental practices have been misunderstood in terms of acquiring knowledge and awareness of the 6th Grade students and the natural environment, knowing and using concepts related to the environment, being aware of environmental problems and making attempts to solve them, being aware of the operation of environmental organizations and participating in environmental activities. The research problem identified as Are alternatif environmental practices effective on the development of environmental sensivity values?. The research method was planned as an action research from qualitative research models. The data of the study, 2N forms, interview records, and evaluation rubrics for each of the alternative environmental practices were collected. The validity and reliability studies of the evaluation rubrics were conducted. The findings of the research were collected with activities such as Empathy, Eko Tourism, Vote Earth, Earth Hour, Earth Hour Lantern Project, Global Warming with Cartoons, Eco Schools Panel Preparations, Action Days Poster Preparation, and so on, through rubrics analysis and analysis through descriptive analysis. As a result, research findings show that students have developed awareness of environmental sensitivity as a value through alternative environmental practices and internalize environmental sensitivity values.
Keywords: Social Studies Lesson; Environmental Education; Sensitivity to Environment; Value Education